Corpses that Speak: Revolutionary Violence and Political Communication in Indonesia. (2nd October 2018) - Peters, Robbie
ABSTRACT: This paper takes the outbreak of the revolution as a starting point to explore the potent power of the dismembered, dispersed and unburied corpse of enemies versus that of the redeemed and commemorated corpse of Indonesian solider heroes. From this starting point, the paper shows how the state formed at the moment of revolutionary violence and that it formed upon the symbology of a constructed genealogy of national heroes. It argues that those heroes belong to the state and contend with an older and more established genealogy of local ancestors that belong to society. The corpse is a key site of this struggle over genealogy. As an unstable symbol that lends itself more to the possession of society than to the state, the corpse has been an insurgent form of political communication that has kept language open, alive and uncontrolled, even during the most authoritarian phases of Indonesian political life.